Hadith #2820 - Sunan Abi Dawud - Abu al-Ahwus, Salam bin Sulaym al-Hanafi أبو الأحوص سلام بن سليم الحنفي; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Rafi' bin Khadij bin Rafi'; Rfa'h bin Rafa'i bin Khdyj رفاعة بن رافع بن خديج; Sa'id bin Masrooq Ath-Thawri سعيد بن مسروق الثوري; Ubaya bin Rafa' bin Rafi' عباية بن رفاعة بن رافع (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) forbade to eat (the meat of animals) slaughtered by the bedouins for vainglory and pride. Abu Dawud said: The narrator Ghundar narrated this tradition as a saying of Ibn ‘Abbas (and not of the Prophet).
Grade: Hasan Sahih

Hadith #2935 - Sunan Abi Dawud - Abdul Rahim bin Sulaiman عبد الرحيم بن سليمان الكناني; Asim bin 'Umar bin Qatada al-Ansari عاصم بن عمر بن قتادة; Ibn Ishaq محمد بن إسحاق بن يسار‎; Mahmud bin Labid bin 'Uqba; Muhammad bin Ibrahim bin al-Harith محمد بن إبراهيم بن الحارث; Rafi' bin Khadij bin Rafi' (Sunan Abi Dawud)
The Prophet (ﷺ) has a secretary named Sijill.
Grade: Da'if

Hadith #3388 - Sunan Abi Dawud - Amr bin Dinar عمرو بن دينار الأثرم الجمحي; ibn Umar; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Rafi' bin Khadij bin Rafi'; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
I Ammar, and Sa’d became partners in what we would receive on the day of Badr. Sa’d then brought two prisoners, but I and Ammar did not bring anything.
Grade: Da'if

Hadith #3391 - Sunan Abi Dawud - Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; al-Laith bin Sa'd الليث بن سعد; Hnzlh bin Qays bin 'Amr حنظلة بن قيس بن عمرو; Ibrahim bin Musa al-Razi al-Fara' إبراهيم بن موسى الرازي الفراء; Isa bin Yonus bin Abi Ishaq عيسى بن يونس بن أبي إسحاق; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Rafi' bin Khadij bin Rafi' (Sunan Abi Dawud)
We used to lease land for what grew by the streamlets and for what was watered from them. The Messenger of Allah (ﷺ) forbade us to do that, and commanded us to lease if for gold or silver.
Grade: Hasan

Hadith #3392 - Sunan Abi Dawud - Hnzlh bin Qays bin 'Amr حنظلة بن قيس بن عمرو; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Rabi'ya bin Abi 'Abdur Rahman; Rafi' bin Khadij bin Rafi' (Sunan Abi Dawud)
I asked Rafi’ b. Khadij about the lease of land for gold and silver (i.e. for dinars and dirhams). There is no harm in it, for the people used to let out land in the time of the Messenger of Allah (ﷺ) for what grew by the current of water and at the banks of streamlets and at the places of cultivation. So sometimes this (portion) perished and that (portion) was saved, and sometimes this remained intact and that perished. There was no (form of) lease among the people except this. Therefore, h
Grade: Sahih

Hadith #3393 - Sunan Abi Dawud - Abdul Malik bin Shu'aib bin al-Laith عبد الملك بن شعيب بن الليث بن سعد; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Aqil bin Khalid bin 'Aqil عقيل بن خالد بن عقيل الأيلي; ibn Umar; Rafi' bin Khadij bin Rafi'; Salim bin 'Abdullah bin 'Umar سالم بن عبد الله بن عمر بن الخطاب; Shu'aib bin al-Laith bin Sa'd شعيب بن الليث بن سعد (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) forbade the leasing of land. I asked: (Did he forbid) for gold and silver (i.e. dinars and dirhams)? He replied: If it is against gold and silver, then there is no harm in it.
Grade: Sahih

Hadith #3394 - Sunan Abi Dawud - Khalid bin al-Harith bin 'Ubaid خالد بن الحارث بن عبيد; Rafi' bin Khadij bin Rafi'; Sa'id bin Abi Sa'id; Sulayman ibn Yasar سليمان بن يسار مولى ميمونة بنت الحارث; Ubaidullah bin 'Umar al-Qawariri عبيد الله بن عمر القواريري; Y'la bin Hkym al-Thqfy يعلى بن حكيم الثقفي (Sunan Abi Dawud)
Ibn ‘Umar used to let out his land till it reached him that Rafi’ b. Khadij al-Ansari narrated that the Messenger of Allah (ﷺ) forbade let out land. So ‘Abd Allah (b. ‘Umar) said: Ibn Khadij, what do you narrate from the Messenger of Allah (ﷺ) about leasing the land? Rafi’ replied to ‘Abd Allah b. ‘Umar: I heard both of my uncles were present in the battle of Badr say, and they narrated it to the members of the family, that the Messenger of Allah (ﷺ) forbade leasing land. ‘
Grade: Sahih

Hadith #3398 - Sunan Abi Dawud - Abu Ja'far al-Khutami, 'Umayr bin Yazid عمير بن يزيد أبو جعفر الخطمي; Muhammad bin Bashar Bindar محمد بن بشار بندار; Rafi' bin Khadij bin Rafi'; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
Rafi’ b. Khadij came to us and said: The Messenger of Allah (ﷺ) forbids you from a work which is beneficial to you ; and obedience to Allah and His Prophet (ﷺ) is more beneficial to you. The Messenger of Allah (ﷺ) forbids you from renting land for share of its produce and he said: If anyone if not in need of his land he should lend it to his brother or leave it. Abu Dawud said: Shu’bah and Mufaddal b. Muhalhal have narrated it from Mansur in similar way. Shu’bah said (in his version)
Grade: Sahih

Hadith #3399 - Sunan Abi Dawud - Abu al-Ahwus, Salam bin Sulaym al-Hanafi أبو الأحوص سلام بن سليم الحنفي; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Rafi' bin Khadij bin Rafi'; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Tarq bin 'Abdur Rahman طارق بن عبد الرحمن البجلي الأحمسي الكوفي (Sunan Abi Dawud)
My uncle sent me and his slave to Sa’id ibn al-Musayyab. We said to him, there is something which has reached us about sharecropping. He replied: Ibn Umar did not see any harm in it until a tradition reached him from Rafi’ ibn Khadij. He then came to him and Rafi’ told him that the Messenger of Allah (ﷺ) came to Banu Harithah and saw crop in the land of Zuhayr. He said: What an excellent crop of Zuhayr is! They said: It does not belong to Zuhayr. He asked: Is this not the land of Zuhayr
Grade: Sahih

Hadith #3401 - Sunan Abi Dawud - Abdur Rahman bin Abi Na'm عبد الرحمن بن أبي نعم; al-Fadl bin Dakayn, Abu Na'eem الفضل بن دكين أبو نعيم الملائي; Harun bin 'Abdullah al-Hamal هارون بن عبد الله بن مروان الحمال; Rafi' bin Khadij bin Rafi' (Sunan Abi Dawud)
I read out (this tradition) to Sa’id b. Ya’qub al-Taliqini, and I said to him: Ibn al-Mubarak transmitted (this tradition) to you from Sa’id Abi Shuja’ who said: ‘Uthman b. Sahl b. Rafi’ b. Khadij narrated it to me saying: I was an orphan being nourished under the guardianship of Rafi’ b. Khadij and I performed Hajj with him. My brother ‘Imran b. Sahl then came to me and said: We rented out land to so-and-so for two hundred dirhams. He said: Leave it, for the Prophet (ﷺ) forbad
Grade: Da'if

Hadith #3402 - Sunan Abi Dawud - Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Ata' bin Abi Rabah عطاء بن أبي رباح; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Rafi' bin Khadij bin Rafi'; Sharayk bin 'Abdullah شريك بن عبد الله النخعي (Sunan Abi Dawud)
Rafi’ had cultivated a land. The Prophet (ﷺ) passed him when he was watering it. So he asked him: To whom does the crop belong, and to whom does the land belong? He replied: The crop is mine for my seed and labour. The half (of the crop) is mine and the half for so-and-so. He said: You conducted usurious transaction. Return the land to its owner and take your wages and cost.
Grade: Da'if

Hadith #3420 - Sunan Abi Dawud - Aban bin Tghlb أبان بن تغلب; al-Sa'ib bin Yazid bin Akht Namr; Ibrahim bin 'Abdullah bin Qariz إبراهيم بن عبد الله بن قارظ; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Rafi' bin Khadij bin Rafi'; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
You have brought what is good from this man. Then they brought a lunatic in chains. He recited Surat al-Fatihah over him three days, morning and evening. When he finished, he collected his saliva and then spat it out, (he felt relief) as if he were set free from a bond. They gave him something (as wages). He then came to the Prophet (ﷺ) and mentioned it to him. The Messenger of Allah (ﷺ) said: Accept it, for by my life, some accept it for a worthless charm, but you have done so far a genuine
Grade: Sahih

Hadith #3426 - Sunan Abi Dawud - Ahmed bin Salah al-Masri أحمد بن صالح المصري; Isma'il bin Muslim bin Aby إسماعيل بن مسلم بن أبي; Muhammad bin Abi Fadayk محمد بن إسماعيل بن مسلم بن أبي فديك; Rafi' bin Khadij bin Rafi' (Sunan Abi Dawud)
Rafi’ ibn Rifa’ah came to a meeting of the Ansar and said: The Prophet of Allah (ﷺ) forbade us (from some things) today, and he mentioned some things. He forbade the earning of a slave-girl except what she earned with her hand. He indicated (some things) with his fingers such as baking, spinning, and ginning.
Grade: Hasan

Hadith #4069 - Sunan Abi Dawud - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; al-Walid bin Kathir al-Makhzumi الوليد بن كثير المخزومي; Hammad bin Usamah حماد بن أسامة - أبو أسامة; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Rafi' bin Khadij bin Rafi' (Sunan Abi Dawud)
A man wearing two red garments passed the Prophet (ﷺ) and gave him a greeting, but he did not respond to his greeting.
Grade: Da'if

Hadith #4518 - Sunan Abi Dawud - Bashayr bin al-Yasar al-Harithi al-Ansar بشير بن يسار مولى بني حارثة; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Muhammad bin 'Ubaid al-Tanafasi محمد بن عبيد بن أبي أمية الطنافسي; Muhaysa bin Mas'ud; Rafi' bin Khadij bin Rafi'; Sahl bin Abi Hathma; Ubaidullah bin 'Umar al-Qawariri عبيد الله بن عمر القواريري; Yahya bin Sa'id al-Ansari يحيى بن سعيد الأنصاري (Sunan Abi Dawud)
“A free man should not be subjected to retaliation in return for a slave.”
Grade: Da'if

Hadith #4522 - Sunan Abi Dawud - al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Rafi' bin Khadij bin Rafi'; Ubaya bin Rafa' bin Rafi' عباية بن رفاعة بن رافع; Yahya bin Sa'id bin Hiyan يحيى بن سعيد بن حيان (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) killed a man of Banu Nadr ibn Malik at Harrah ar-Righa’ at the bank of Layyat al-Bahrah. The transmitter Mahmud (ibn Khalid) also mentioned the words along with the words “at Bahrah” “the slayer and the slain were from among them”. Mahmud alone transmitted in this tradition the words “at the bank of Layyah”.
Grade: Da'if